Prolonged effect of GlycoPEGylated rFVIIa (40k-PEG-rFVIIa) in rabbits correlates to activity in plasma - Johansen, Peter B.; Bjørn, Søren E.; Agersø, Henrik; Thorup, Inger; Hermit, Mette B.; Sørensen, Brit B.; Stennicke, Henning R.; Ezban, Mirella; Tranholm, Mikael (Thrombosis and Haemostasis, 2010)
The pharmacokinetics and pharmacodynamics of 40k-PEG-rFVIIa, a GlycoPEGylated derivative of recombinant wild-type FVIIa, were compared with rFVIIa in rabbits. The procoagulant effect was determined as the weight of the clot formed in a defined segment of a facial vein. A time course study was conducted where ligation was made 10 minutes, 12 or 24 hours after i.v. injection of equimolar doses of 40k-PEG-FVIIa or rFVIIa (2 mg/kg). This dose was selected based on a dose response study and a duration of effect study with rFVIIa. The clot weight increased with increasing doses of rFVIIa, and the duration of effect correlated with the plasma FVIIa clot activity. The plasma half-life of 40k-PEG-rFVIIa measured as FVIIa clot activity was found to be 25 hours, which was 5–6 times longer than rFVIIa. The aPTT and PT were reduced, and the measured increase in thrombin-antithrombin correlated to the effect on clot formation. Thus, the effect was similar at ligation 10 minutes after administration of 40k-PEG-rFVIIa or rFVIIa. At 12 hours, the effect of rFVIIa was absent while significant effect was seen 12 and 24 hours post dosing with 40k-PEG-rFVIIa. No consumption of platelets or fibrinogen was found and no thrombi formation was seen in histological examination of various organs. In conclusion, 40k-PEG-rFVIIa has shown prolonged duration of effect that correlated to various plasma markers and FVIIa clot activity. In perspective, the data support further clinical development of 40k-PEG-rFVIIa to potentially become a long-acting recombinant treatment option for prophylaxis in haemophilia patients with inhibitors.
Keywords: Coagulation activity; glycoPEGylated rFVIIa; venous stasis; rabbits